The Synthesis and Properties of a New Carrier for Paclitaxel and Doxorubicin Based on the Amphiphilic Copolymer of N‐vinyl‐2‐pyrrolidone and Acrylic Acid. Issue 17 (15th July 2022) - Nechaeva, Anna M.; Artyukhov, Alexander A.; Luss, Anna L.; Shtilman, Mikhail I.; Svistunova, Alina Yu.; Motyakin, Mikhail V.; Levina, Irina I.; Krivoborodov, Efrem G.; Toropygin, Ilya Yu.; Chistyakov, Evgeniy M.; Tsatsakis, Aristides M.; Gurevich, Leonid; et al.
Abstract: This paper deals with the development of polymeric nanocarriers based on amphiphilic copolymers of N ‐vinyl‐2‐pyrrolidone and acrylic acid of various molecular weights synthesized through the AIBN‐initiated radical copolymerization of N ‐vinyl‐2‐pyrrolidone and acrylic acid in the presence of n ‐octadecyl mercaptan. The structure of the copolymers is characterized by 1 Н NMR, 13 С NMR, IR and MALDI‐TOF MS spectroscopy. It is shown that the length of the hydrophilic block defines the size of the nanoaggregates while impacting the steric stabilization efficiency and the probability of the interchain hydrogen bond formation. The hydrogen bonds formation between the residues of N ‐vinyl‐2‐pyrrolidone and acrylic acid is in agreement with the reduction of the ζ‐potential of the nanoaggregates and the critical aggregation concentrations upon increasing the molecular weight. The presence of acrylic acid residues in the amphiphilic macromolecules leads to a higher affinity for doxorubicin and slow partial release of doxorubicin bonded with the aggregates' corona, which is helpful for reducing its cardiac toxicity. Nanoaggregates with a paclitaxel‐loaded hydrophobic core are obtained, showing the possibility of dual loading. The amphiphilic copolymers of N ‐vinyl‐2‐pyrrolidone and acrylic acid containing an n ‐octadecyl thio end group are thus promising candidates for combination cancer therapy with immobilized anti‐cancer drugs, paclitaxel, and doxorubicin. Abstract : Amphiphilic copolymers of N ‐vinyl‐2‐pyrrolidone and acrylic acid with a hydrophobic n ‐octadecyl thio end‐group capable of self‐assembly in water and noncovalent immobilization of paclitaxel and doxorubicin are synthesized. Diameters of aggregates are defined by interplay of steric stabilization and interchain coupling through hydrogen bonding. The aggregates are promising carriers for combination therapies for late‐stage cancer and decreasing cardiac toxicity of doxorubicin.